A diachronic analysis of explicit definitions and implicit conceptualizations of language learning strategies. (December 2021) - Thomas, Nathan; Bowen, Neil Evan Jon Anthony; Rose, Heath
Abstract: The field of language learning strategies (LLS) has grown significantly, experiencing many twists and turns over the years. Consequently, this study takes stock of, and reports on, definitional and conceptual changes, because how we define a concept can greatly affect its impact on teaching and research. We collected 461 journal articles from prominent databases and divided them into three time periods marked by major developments in the field: 1975–1990, 1991–2005, and 2006–2019. We then used content analysis to categorize, code, and explore explicit definitions found in the articles and various corpus-based techniques on the full texts to investigate implicit conceptualizations of LLS within and across these time periods. The findings indicate that elements of self-directedness (e.g., self-regulation, agency, and autonomy) are increasingly prevalent in researchers' conceptualizations over time. The findings also highlight trends in language related to self-directedness, especially in the way strategies are portrayed to be operationalized by learners and in their intended purpose(s). Based on our findings, we argue for a change in thinking—from the ideal to the actual—in LLS conceptualizations and call for reconceptualized roles of teachers and students that are more representative of and compatible with instructed language learning contexts.